Cerebrospinal fluid inflammatory markers in patients with multiple sclerosis: a pilot study - Matejčíková, Z; Mareš, J; Přikrylová Vranová, H; Klosová, J; Sládková, V; Doláková, J; Zapletalová, J; Kaňovský, P (Journal of neural transmission (Vienna, Austria, 2015)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the central nervous system. Autoimmune inflammation is common in the early stages of MS. This stage is followed by the neurodegenerative process. The result of these changes is axon and myelin breakdown. Although MS is according to McDonald's revised diagnostic criteria primarily a clinical diagnosis, paraclinical investigation methods are an important part in the diagnosis of MS. In common practice, magnetic resonance imaging of the brain and spinal cord, examination of cerebrospinal fluid (CSF) and examination of visual evoked potentials are used. There are an increasing number of studies dealing with biomarkers in CSF and their role in the diagnosis and treatment of MS. We hypothesized that the levels of some markers could be changed in MS in comparison with controls. We studied five inflammatory markers [interleukin-6 (IL-6), interleukin-8, interleukin-10 (IL-10), beta-2-microglobulin, orosomucoid]. CSF and serum levels of inflammatory markers were assessed in 38 patients with newly diagnosed MS meeting McDonald's revised diagnostic criteria and in 28 subjects as a control group (CG). Levels of beta-2-microglobulin and interleukin-8 in CSF were found to be significantly higher in MS patients in comparison to CG (p < 0.001 resp. p = 0.007). No differences in other CSF markers (IL-6, IL-10 and orosomucoid) and serum levels of all markers between both groups were found. The levels of two studied inflammatory markers were found to be increased at the time of first clinical symptoms of MS. Research on the role of inflammatory and neurodegenerative markers in MS should continue.
Keywords: beta-2-mikroglobulin; Male; Statistics, Nonparametric; neparametrická statistika; Multiple Sclerosis; pilotní projekty; cytokiny; imunoanalýza; Adult; dospělí; mužské pohlaví; orosomukoid; lidé; ženské pohlaví; Humans; Immunoassay; beta 2-Microglobulin; Cytokines; Pilot Projects; Female; Orosomucoid; lidé středního věku; roztroušená skleróza; Middle Aged